A Novel Alkylated Indacenodithieno[3,2-b]thiophene-based Polymer for High-performance Field Effect Transistors - Heeney,MJ; Han,Y; Fei,Z; McCulloch,I; Stingelin,N; Treat,N; Anthopoulos,T; Faber,H; Zhang,W; Zhu,X; Feng,Y (Advanced Materials, 2015)
A novel rigid donor monomer, indacenodithieno[3,2-b]thiophene (IDTT), containing linear alkyl chains is reported. Its copolymer with benzothiadiazole is an excellent p-type semiconductor, affording a mobility of 6.6 cm² V¹ s¹ in top-gated field-effect transistors with pentafluorobenzenethiol-modified Au electrodes. Electrode treatment with solution-deposited copper(I) thiocyanate (CuSCN) has a beneficial hole-injection/electron-blocking effect, further enhancing the mobility to 8.7 cm² V¹ s¹.